Black beauty - Freeman, Michael Lacey; Sewell, Anna Aurilia, Davide (ELI s.r.l. Recanati MC, Italy, 2017)
A horse tells the story of his life in nineteenth-century England, and his treatment under many different masters, from a kind country squire to all kinds of drivers when he was let out for hire